Myeloid-Epithelial-Reproductive Receptor Tyrosine Kinase and Milk Fat Globule Epidermal Growth Factor 8 Coordinately Improve Remodeling After Myocardial Infarction via Local Delivery of Vascular Endothelial Growth Factor. Issue 9 (1st March 2016) - Howangyin, Kiave-Yune; Zlatanova, Ivana; Pinto, Cristina; Ngkelo, Anta; Cochain, Clément; Rouanet, Marie; Vilar, José; Lemitre, Mathilde; Stockmann, Christian; Fleischmann, Bernd K.; Mallat, Ziad; Silvestre, Jean-Sébastien
Abstract : Background—: In infarcted heart, improper clearance of dying cells by activated neighboring phagocytes may precipitate the transition to heart failure. We analyzed the coordinated role of 2 major mediators of efferocytosis, the myeloid-epithelial-reproductive protein tyrosine kinase (Mertk) and the milk fat globule epidermal growth factor (Mfge8), in directing cardiac remodeling by skewing the inflammatory response after myocardial infarction. Methods and Results—: We generated double-deficient mice for Mertk and Mfge8 (Mertk −/− /Mfge8 −/− ) and challenged them with acute coronary ligature. Compared with wild-type, Mertk-deficient (Mertk −/− ), or Mfge8-deficient (Mfge8 −/− ) animals, Mertk −/− /Mfge8 −/− mice displayed greater alteration in cardiac function and remodeling. Mertk and Mfge8 were expressed mainly by cardiac Ly6C High and Low monocytes and macrophages. In parallel, Mertk −/− /Mfge8 −/− bone marrow chimeras manifested increased accumulation of apoptotic cells, enhanced fibrotic area, and larger infarct size, as well as reduced angiogenesis. We found that the abrogation of efferocytosis affected neither the ability of circulating monocytes to infiltrate cardiac tissue nor the number of resident Ly6C High and Ly6C How monocytes/macrophages populating the infarcted milieu. In contrast, combined Mertk and Mfge8 deficiency in Ly6C High /Ly6C Low monocytes/macrophages either obtained from in vitro differentiation of bone marrow cells or isolated from infarcted hearts altered their capacity of efferocytosis and subsequently blunted vascular endothelial growth factor A (VEGFA) release. Using LysMCre + /VEGFA fl/fl mice, we further identified an important role for myeloid-derived VEGFA in improving cardiac function and angiogenesis. Conclusions—: After myocardial infarction, Mertk- and Mfge8-expressing monocyte/macrophages synergistically engage the clearance of injured cardiomyocytes, favoring the secretion of VEGFA to locally repair the dysfunctional heart. Abstract : Supplemental Digital Content is available in the text.